KAPABILITAS APARAT DESA DALAM PENGELOLAAN DANA DESA - Pramudi Harsono (Universitas Sultan Ageng Tirtayasa, 2016)
The village as a spearhead of development has an important role indevelopment. With the birth of the Law of vilage No. 6 / 2014 opened a greatopportunity for the village to get a sizeable village funds. The village as an autonomousregion has the authority to remedy to manage the funds of the village, but the largeamount of funds that must be managed professionally and appropriately. Meanwhilecapabilities village head and village in Serang District still is lacking. The purpose ofthis study was to analyze the capabilities of the village in managing the funds of thevillage. This study is a qualitative study, by observation and analysis of documents.Guiding theory is a theory of Leonard and Barton (2002), namely: Based on theknowledge and skills, managerial systems, Technical Systems, Values and Norms. Theresults of the study explained that the knowledge and skills capability village head andvillage in Pandeglang in the management of village fund allocation is still lacking,especially the skill and expertise in accounting, financial reporting and accountability.Managerial capabilities are lacking because the village head in planning some of thevillage chief has yet to make programs according to priorities. Technical capabilitiesconcerning the financial management of the State is still lacking. Most treasurervillages do not have enough knowledge in financial management and not a backgroundof expertise such as accounting vocational graduates. Financial management is stillmanual. Capabilities Values and Norms. Village Head in Pandeglang in general it canbe said either they already have good values and norms that come from the community.It's just that their values and norms of society can not be performed / implemented inorganizational life.